The challenge of global capitalism : the world economy in the 21st century - Gilpin, Robert; Gilpin, Jean M. (Princeton, N.J. : Chichester : Princeton University Press, 2002)
The author maintains that global capitalism and economic globalization have rested and must continue to rest on a secure political foundation. However, this foundation has eroded since the end of the Soviet threat. To ensure survival of the global economy, Gilpin concludes, the United States and other major powers must recommit themselves to working together to rebuild its weakened political foundation
Originally published: 2000.
Includes bibliographical references and index.
oif 19/07/16
Loans
Keywords: International economic relations; International relations; Structural adjustment (Economic policy); Globalization; Capitalism; International trade